BIOECOLOGICAL AND MORPHOLOGICAL CHARACTERISTICS OF LICORICE (GLYCYRRHIZA GLABRA L.) - Baltabaev, Muratbay Torebaevich; Abillayeva, Shahzoda Farxatovna (SCIENCE and SOCIETY, 2026)
The article examines the bioecological and morphological characteristics of the licorice plant – Glycyrrhiza glabra L., providing information on the plant's natural distribution areas, climate adaptation, vegetative and generative reproduction, and the characteristics of its root system. At the same time, the significance of licorice in the national economy and its medicinal properties are analyzed.
Keywords: medicinal plant; root; stem; leaf; flower; bud; seed; morphological features; polycarpic; rhizome; vegetative propagation; perennial plant; tree; shrub; herbaceous plant; formation; association; underground and above-ground parts